Influence of carbon emission trading policy on residents' health in China - Bingnan Guo; Yu Feng; Yu Wang; Ji Lin; Jingyi Zhang; Shan Wu; Ru Jia; Xiaolei Zhang; Han Sun; Wei Zhang; Wei Li; Hao Hu; et al. (Frontiers in Public Health, 2022)
Residents' health is the basic condition for economic and social development. At present, China's environmental pollution problem is becoming increasingly serious, which not only hinders sustainable economic and social development, but also poses a major threat to public health. Therefore, based on the carbon emissions trading policy implemented in China, this paper explores this policy's impact on residents' health using the DID model and illustrates the moderating effect of environmental pollution. The results show that (1) carbon emissions trading policies can promote the improvement of residents' health; (2) the effect is stronger for western regions and provinces with smaller population sizes after taking control variables into consideration; and (3) environmental pollution has a significant moderating effect on the relationship between carbon emissions trading and residents' health. This research serves as an important reference for expanding the scope of the policy pilot, reducing pollutant emissions, and improving the health of the population.